Effects of Display Curvature and Task Duration on Proofreading Task Performance, Visual Fatigue, Visual Discomfort, and Display Satisfaction. (September 2016) - Park, Sungryul; Yi, Jihhyeon; Choi, Donghee; Lee, Songil; Kyung, Gyouhyung; Choi, Byeonghwa; Lee, Ja Eun; Lee, Seungbae
With more curved display products in the market and more exposure to such products, it is necessary to examine the effects of display curvature and task duration from the ergonomics perspective. The current study examined the effects of these two factors on visual performance, visual fatigue, visual discomfort, and display satisfaction during proofreading tasks. We incorporated five display curvatures (600R, 1140R, 2000R, 4000R, and flat) and five task durations (0, 15, 30, 45, and 60 min). Each of 50 individuals completed a 1-hr proofreading task at one of five display curvature conditions. The horizontal viewing distance was fixed at 600mm. Proofreading performance (speed and error rate), subjective visual fatigue [on ECQ (Eye Complaint Questionnaire)], physiological visual fatigue [CFF (Critical Fusion Frequency), blink duration, and blink frequency], visual discomfort (on VAS), and display satisfaction (on VAS) were measured. The highest mean proofreading speed was at 600R. The mean proofreading speed and error rate increased by 15.5% and 22.3%, respectively, over the 1-h task. The mean ECQ score and visual discomfort increased by 188.6% and 107.2% during 45 and 60 min of the task, respectively. The mean CFF and display satisfaction decreased by 0.49Hz and 11.2% during 15 and 15-45 min of the task. A polynomial regression model for subjective visual fatigue was developed (adjusted R2 = 0.6). These findings can be used when determining ergonomic display curvatures and predicting visual fatigue.